2014
DOI: 10.1021/nl404454h
|View full text |Cite
|
Sign up to set email alerts
|

Why Lead Methylammonium Tri-Iodide Perovskite-Based Solar Cells Require a Mesoporous Electron Transporting Scaffold (but Not Necessarily a Hole Conductor)

Abstract: CH3NH3PbI3-based solar cells were characterized with electron beam-induced current (EBIC) and compared to CH3NH3PbI(3-x)Clx ones. A spatial map of charge separation efficiency in working cells shows p-i-n structures for both thin film cells. Effective diffusion lengths, LD, (from EBIC profile) show that holes are extracted significantly more efficiently than electrons in CH3NH3PbI3, explaining why CH3NH3PbI3-based cells require mesoporous electron conductors, while CH3NH3PbI(3-Clx ones, where LD values are com… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

30
489
0
3

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 554 publications
(527 citation statements)
references
References 22 publications
30
489
0
3
Order By: Relevance
“…Therefore, the FTO layers are the n þ þ electrodes. Reports in literature have shown that some lead halide perovskite solar cells behave as p-i-n cells 3,[16][17][18] . Our lead halide perovskites thin films are highly resistive and have low carrier concentrations, typically below the sensitivity of our Hall measurement system (B10 14 cm À 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, the FTO layers are the n þ þ electrodes. Reports in literature have shown that some lead halide perovskite solar cells behave as p-i-n cells 3,[16][17][18] . Our lead halide perovskites thin films are highly resistive and have low carrier concentrations, typically below the sensitivity of our Hall measurement system (B10 14 cm À 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…It is worth noting here that for devices incorporating mesoporous TiO 2 photoanodes, the neat tri-iodide perovskite functions effi ciently without the need for the extended diffusion length of the photoexcited species. [ 11 ] This is a result of the interpenetrated nature of the collection photoanode, which exhibits pore sizes at the order of tens of nanometers, and in effect reduces the distance electrons must travel to this magnitude before being collected. In the case of planar heterojunctions, electrons must travel the entire thickness of the fi lm, which can sometimes exceed hundreds of nanometers and thus extended diffusion lengths are a requirement for effi cient operation.…”
Section: Doi: 101002/aenm201400355mentioning
confidence: 99%
“…[ 17,18 ] MAPbI 3 also appears to exhibit only shallow trap-levels and although the grain boundaries have recently been shown to induce nonradiative decay, [ 19 ] regions only a few tens of nm away from the grain boundaries appear to be unaffected. [ 20,21 ] Furthermore, low Urbach energies, which are extracted from near band edge optical absorption measurements and serve as a benchmark for crystalline phase disorder, indicate low disorder and sharp band edges for lead tri-halide perovskites (15-23 meV). [ 22,23 ] All of these properties contribute to high open-circuit voltages, long charge-carrier lifetimes, and micrometer diffusion lengths, which are crucial for planar-hetero junction photovoltaics.…”
mentioning
confidence: 99%